BODY MASS INDEX RELATIONS WITH THE DIFFICULTIES AND COMPLICATIONS OF PERCUTANEOUS NEPHROLITHOTOMY - Prapiska, Fauriski Febrian; Hardjowijoto, Sunaryo; Soebadi, Doddy M; Djojodimedjo, Tarmono (Indonesian Journal of Urology, 2016)
Objective: To identified outcomes and complications of percutaneous nephrolithotomy (PCNL) in patients of various body mass indices (BMI) to determine the safety of this procedure in patients with elevated BMI.Material & methods: The analytic observational prospective study of patients who underwent PCNL between February to July 2015 in the operating room Soetomo General Hospital Surabaya. Specifically, BMI, stone-free rates, difficulties duringsurgery, complications, and Clavien score were assessed. We evaluate the independent contribution of BMI as a predictor of outcomes. Results: There were 35 selected patients with kidney stone and planned to PCNL, 20 patients were included and 15 patients were excluded from this study. The patients consisted of 10 men (50%) and 10 women (50%). Mean age was 47.55 years (range 33-75). There were 4 patients with diabetes (20%), and 10 patients with hypertension (50%). Mean stone size was 23.30 mm. Stone location was 11 patients (55%) in the right kidney, and 9 patients (45%) in the left. There were 12 patients (60%) with a single stone, and 8 patients (40%) with multiple stones. BMI values were distributed as follows,underweight 1 patient (5%), normoweight 7 patients (35%), overweight 6 patients (30%), obesity 6 patients (30%). Mean skin to stone distance (SSD) was 87.56 mm. Stone free rate was 55%, and difficulties during surgery only seen in 1 patient (5%) bleeding profusely and open surgery was performed. Clavien score in these patients were grade I in 11 patients (55%), grade II in 7 patients (35%), and grade IIIB in 2 patients (10%). The BMI had no significant effect with Intra operative and postoperative difficulties (0.390. p <0.05. CI 95%). However the lower stone free rate had significant effect (0.040. p <0.05. CI 95%).Conclusion: BMI had no significant effect with Intraoperative and postoperative difficulties in PCNL.However, the lower stone-free rate risk associated with elevated BMI was significant.